2019
DOI: 10.1136/injuryprev-2018-043080
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and firearm homicide in the US: a county-level cohort study

Abstract: ObjectiveIncome inequality has been rising in the US and thought to be associated with violence especially homicide. About 75% of homicides involve firearms. We quantified the association between county-level income inequality and all-race/ethnicity and race/ethnicity-specific firearm homicide rates among individuals aged 14–39 years.MethodsWe conducted a cohort study of US counties to examine the association of Gini Index (ranging from 0 [perfect income equality] to 1.0 [perfect income inequality]) separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 28 publications
1
44
0
3
Order By: Relevance
“…In a study among Chicago neighborhoods, there was a similar correlation of 0.75 between income inequality and the homicide rate [86]. A recent ecological, lagged cross-sectional study [22] observed a positive association between US county-level income inequality and the homicide rate, although the association only attained significance at the 5% level in black individuals. Each 1-SD unit increase in the county-level Gini coefficient was related to a 9% increase in the county-level firearm homicide rate among black individuals 5 to 15 years later, controlling for county-level age, gender, and race/ethnicity composition, crime rate, deprivation, social capital, urbanicity, and firearm ownership [22].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a study among Chicago neighborhoods, there was a similar correlation of 0.75 between income inequality and the homicide rate [86]. A recent ecological, lagged cross-sectional study [22] observed a positive association between US county-level income inequality and the homicide rate, although the association only attained significance at the 5% level in black individuals. Each 1-SD unit increase in the county-level Gini coefficient was related to a 9% increase in the county-level firearm homicide rate among black individuals 5 to 15 years later, controlling for county-level age, gender, and race/ethnicity composition, crime rate, deprivation, social capital, urbanicity, and firearm ownership [22].…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, to date, findings from empirical studies of income inequality and homicide have been mixed. Some studies have confirmed the theorized positive association [22,74], whereas other studies have found no association [75] or even an inverse relationship [61,76,77]. Possible explanations for this mixed evidence include the ecological and cross-sectional design of many of the studies, a study design which is prone to confounding and reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, virtually all of the counties characterized by low inequality in 1970 had transitioned to moderate or high levels of inequality by 2016. Fifth and finally, increases in the average level of inequality among counties were paralleled by non-trivial growth in the share of populations residing in high-inequality places and thus potentially subject to the adverse social and epidemiological effects of such places (Eckenrode et al 2014;Monnat 2018;Rowhani-Rahbar et al 2019). This growth has been particularly dramatic among the metropolitan population, such that the predominance of non-metropolitan counties in high-inequality contexts in 1970 was reversed by 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth and finally, increases in the average level of inequality among counties were paralleled by non‐trivial growth in the share of populations residing in high‐inequality places and thus, potentially subject to the adverse social and epidemiological effects of such places (Eckenrode et al 2014; Monnat 2018; Rowhani‐Rahbar et al 2019). This change has been particularly dramatic among the metropolitan population, which had very little (1.0 percent) exposure to high inequality (and 30.0 percent exposure to low inequality) in 1970.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation